PENGEMBANGAN MEDIA POWERPOINT INTERAKTIF UNTUK KEMAMPUAN MENULIS MATA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Azzami, Rayke; Dafit, Febrina (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to develop an interactive PowerPoint as a learning medium for Indonesian language instruction for fourth-grade students at SDN 138 Pekanbaru. The research employed a Research and Development (R&D) approach consisting of three stages: analysis, design, and development. The subjects involved six expert validators, as well as a teacher and fourth-grade students. Data were collected using validation sheets from material experts, media experts, and language experts, along with questionnaires on teacher and student responses. The data were analyzed using both qualitative and quantitative techniques. The results indicated that the developed PowerPoint media for teaching deductive, inductive, and mixed paragraphs was categorized as “very valid” based on expert evaluations. In addition, responses from both teachers and students were rated in the “very good” category. In conclusion, the interactive PowerPoint media developed in this study is highly valid and well-received, making it suitable as an effective learning medium for Indonesian language instruction at the elementary school level.